2011
DOI: 10.1353/aad.2011.0017
|View full text |Cite
|
Sign up to set email alerts
|

Social-Emotional Functioning of Elementary-Age Deaf Children: A Profile Analysis

Abstract: Discussion and study of the social-emotional development of deaf and hard of hearing children, though extensive, has yet to provide an accurate understanding of the differences between deaf and hearing children. Consequently, the goal of the researchers was to conduct a profile analysis to determine similarities and differences between the two groups. The sample consisted of 20 hearing and 20 deaf children ages 8–11 years. All of the deaf children were enrolled in a Simultaneous Communication magnet program. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Deaf children and hearing children did not differ significantly on the first four constructs but did on the school interest/assertiveness and task orientation constructs. Deaf children also reported more difficulty in making friends [76].…”
Section: Introductionmentioning
confidence: 99%
“…Deaf children and hearing children did not differ significantly on the first four constructs but did on the school interest/assertiveness and task orientation constructs. Deaf children also reported more difficulty in making friends [76].…”
Section: Introductionmentioning
confidence: 99%
“…In a survey of 111 Swedish deaf and hard-of-hearing children, Mejstad, Heiling, and Svedin (2008, 2009) found that teachers' ratings of students’ social competence were significantly lower than those offered by the students and their parents (McFayden-Ketchum & Dodge, 1998); the latter two did not differ from each other. Vogel-Walcutt, Schatschneider, and Bowers (2011) conducted a profile analysis of teachers’ ratings, parents’ ratings, children’s self-reports, children interviews, and researcher observations. Responses from 20 deaf and 20 hearing children aged 8–11 years were organized into six different constructs: externalizing behaviors, internalizing behaviors, social skills, loneliness, school interest/assertiveness, and task orientation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is known that deaf people are a linguistic minority (Martins, 2012), which means that the differences arising between deaf and hearing individuals can increase as they belong to two different cultures, which differ both by in the matter of language and in specific matters (exclusion, social segregation and limitations). However, this result contradicts strong and Kirk (1938) and Vogel-Walcutt et al (2011). Thus, these differences in the development of a deaf child might be the cause of such deficits, especially since interaction can be limited and the quality of acquisition of social models might be reduced (Marschark, 2018;Matson, 2017), possibly leading to limitations in communication (Gianoto, Gianotto, & Marques, 2016), since the deaf participants of this research come from hearing families.…”
Section: Discussionmentioning
confidence: 62%